Reducing Water Vapor Permeability of Poly(lactic acid) Film and Bottle through Layer-by-Layer Deposition of Green-Processed Cellulose Nanocrystals and Chitosan - Katalin Halász; Yanin Hosakun; Levente Csóka (International Journal of Polymer Science)
Layer-by-layer electrostatic self-assembly technique was applied to improve the barrier properties of poly(lactic acid) (PLA) films and bottles. The LbL process was carried out by the alternate adsorption of chitosan (CH) (polycation) and cellulose nanocrystals (CNC) produced via ultrasonic treatment. Four bilayers (on each side) of chitosan and cellulose nanocrystals caused 29 and 26% improvement in barrier properties in case of films and bottles, respectively. According to the results the LbL process with CH and CNC offered a transparent “green” barrier coating on PLA substrates.